2016
DOI: 10.1007/s11244-016-0660-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Reactant and Product Adsorption Energies in the Selective Oxidative Coupling of Alcohols to Esters on Au(111)

Abstract: Gold-based heterogeneous catalysts have attracted significant attention due to their selective partial oxidation capabilities, providing promising alternatives for the traditional industrial homogeneous catalysts. In the current study, the energetics of adsorption/desorption of alcohols (CH3OH/methanol, CH3CH2OH/ethanol, CH3CH2CH2OH/n-propanol) and esters (HCOOCH3/methyl formate, CH3COOCH3/methyl acetate, and CH3COOCH2CH3/ethyl acetate) on a planar Au(111) surface was investigated in conjunction with oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Even though ab initio calculations have long indicated that a C–C–C–O gauche conformation in 1-propanol represents the global minimum, it is still quite common to find studies of 1-propanol adsorption and reactivity that focus solely on the anti conformer. For instance, very recent computational studies of 1-propanol adsorption on nanosheets, rutile, Au(111), zeolites, and tungsten carbide, among other surfaces, have considered only the all- anti conformer, without exploration of other conformers of similar or even lower energy. The notion that the all- anti structure of 1-propanol is the only conformer with significant thermal population is likely a direct inference from the more studied linear alkanes, in which gauche conformers are substantially higher in energy .…”
Section: Introductionmentioning
confidence: 99%
“…Even though ab initio calculations have long indicated that a C–C–C–O gauche conformation in 1-propanol represents the global minimum, it is still quite common to find studies of 1-propanol adsorption and reactivity that focus solely on the anti conformer. For instance, very recent computational studies of 1-propanol adsorption on nanosheets, rutile, Au(111), zeolites, and tungsten carbide, among other surfaces, have considered only the all- anti conformer, without exploration of other conformers of similar or even lower energy. The notion that the all- anti structure of 1-propanol is the only conformer with significant thermal population is likely a direct inference from the more studied linear alkanes, in which gauche conformers are substantially higher in energy .…”
Section: Introductionmentioning
confidence: 99%
“…Here the uppercase letter refers to the CCCO dihedral angle and the lowercase letter corresponds to the CCOH dihedral angle. Most studies of n -PrOH adsorption and reactivity have focused solely on anti n -PrOH, even though ab initio calculations indicate that the global minimum of n -PrOH is the gauche conformation. Rotation around the CCOH dihedral interconverts between the a and g conformers through barriers of ∼500 K. However, interconversion of G and A species involves rotation of the alkyl group with a barrier calculated to be 1600 K. , Although the energetic differences between conformers are small (see Table ), which would suggest efficient thermalization, it is possible that at low temperatures a single conformer may be preferentially formed without the ability to interconvert between species given the high barriers that separate them. Recent high-level calculations by Troya mapped the potential energy profile of the hydrogen abstraction reaction between O­( 3 P) and all conformational isomers of n -PrOH .…”
mentioning
confidence: 99%
“…For the conformers interacting with the Ag 19 cluster, geometry optimization indicates that all five conformers bond to an atop site as illustrated in Figure . Bonding through the O atom to an atop site was also reported in a DFT study of 1-propanol on Au(111) . The adsorption energies and adsorption energies relative to the most strongly bound Tt conformer are given in Table for two basis sets.…”
Section: Resultsmentioning
confidence: 59%
“…Bonding through the O atom to an atop site was also reported in a DFT study of 1-propanol on Au(111). 14 The adsorption energies and adsorption energies relative to the most strongly bound Tt conformer are given in Table 2 for two basis sets. The Tt conformer is calculated to be the most stably adsorbed conformer for both basis sets, while the Gg′ and Gg conformers have the second and third highest adsorption energies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation